Face-specific negative bias of aesthetic perception in depression: Behavioral and EEG evidence - Chen, Zhitang; Wang, Zhenghua; Shen, Yuhua; Zeng, Suhua; Yang, Xiangyu; Kuang, Yifang; Dou, Zheng; Wang, Lihui; Li, Weidong (Frontiers in Psychiatry, 2023)
Symptoms of depression are associated with the dysfunction of neural systems such as the emotion, reward system, and the default mode network. These systems were suggested by the model of neuroaesthetics as key contributions to aesthetic experience, leading to the prediction of atypical aesthetic orientation in depression. Here we investigated the aesthetic characteristics of depression and the corresponding neural underpinnings. Fifty-two (25 depression patients, 27 healthy controls) participants were asked to make aesthetic judgments on faces and landscapes in an electroencephalographic (EEG) experiment. Our results indicate that relative to the controls, the depression tended to give ugly judgments and refrained from giving beautiful judgments, which was observed only for faces but not for landscapes. We also found that the face-induced component N170 was more negative in the depression group than the control group for ugly and neutral faces. Moreover, the aesthetic evaluation of ugly faces was associated with decreased N200 negativity in the depression group than in the control group, while the evaluation of beautiful faces was associated with decreased brain synchronization at the theta band. These results suggested a face-specific negative aesthetic bias in depression which can help to design and develop aesthetics-oriented schemes in assisting the clinical diagnosis and therapy of depression.